2001
DOI: 10.1179/joc.2001.13.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Locoregional Application of Mitoxantrone in Patients with Early Breast Carcinoma

Abstract: The aim of this study was to investigate the clinical and morphological aspects of drug diffusion and efficacy after perioperative locoregional application of mitoxantrone in patients with early breast cancer. Mitoxantrone was injected at a dose of 0.5 ml (1.0 mg) in two sites around the tumor in 37 patients. Intraoperative inspection of mitoxantrone diffusion in breast and axillary tissues was carried out by blue color of the chemotherapeutic drug. Investigations of reactive morphological changes in axillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…That study clearly established that preoperative bronchoscopic injection of tracer/marker agents into the tumour and adjacent normal bronchial mucous membrane results in their transport to sentinel and regional lymph nodes within 6 h. The migration of cytotoxic drugs injected similarly should follow the same pathway and kill malignant metastatic cells without systemic drug toxicity. The clinical findings of Baitchev et al [59] . with intratumoural injection of blue mitoxantrone in early breast cancer also supports our hypothesis that a chromophoric cancer drug such as mitoxantrone (with a molecular weight comparable with staining dyes) will be transported to the sentinel and regional lymph nodes through lymphatic drainage immediately following the bronchoscopic injection into either the tumour or the tissue adjacent to the tumour site.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…That study clearly established that preoperative bronchoscopic injection of tracer/marker agents into the tumour and adjacent normal bronchial mucous membrane results in their transport to sentinel and regional lymph nodes within 6 h. The migration of cytotoxic drugs injected similarly should follow the same pathway and kill malignant metastatic cells without systemic drug toxicity. The clinical findings of Baitchev et al [59] . with intratumoural injection of blue mitoxantrone in early breast cancer also supports our hypothesis that a chromophoric cancer drug such as mitoxantrone (with a molecular weight comparable with staining dyes) will be transported to the sentinel and regional lymph nodes through lymphatic drainage immediately following the bronchoscopic injection into either the tumour or the tissue adjacent to the tumour site.…”
Section: Discussionsupporting
confidence: 86%
“…Such first‐pass transport of drug to the regional lymph nodes therefore has important implications for locoregional therapy of metastasis. Indeed, Baitchev et al [59] . in their clinical study in early breast cancer, have observed the first‐pass transport of the blue‐staining mitoxantrone to the regional lymph nodes.…”
Section: Detection and Mapping Of Human Sentinel Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sentinel nodes represent the initial lymphatic site for tumor migration and therefore the locus of initial malignant cell dissemination [76][77][78]. e. An immuno-therapeutic effect due to antigenic expression by a large mass of tumor cell debris [79,80]. f. The local radio-sensitizing effect of intratumoral cisplatin which enhances the efficacy of the radiotherapy [81][82][83].…”
Section: Asymptomatic Lesions With Less Than 50% Obstruction Of Majormentioning
confidence: 99%
“…Although we have related the localized necrosis to the EPI distribution during the Co-CACH procedure, we didn't actually label the EPI and therefore we could have used a colored anthracycline cytotoxic. 46 Finally, we didn't compare the ablative effect of ''conservative'' CA with our Co-CACH technique, since CA without safety margin has long been demonstrated unable to fully eradicate a solid tumor. 47,48 We purposely didn't use a prefreezing IT administration of the therapeutic fluid, given that previous in vitro 16 and clinical applications had shown that an LMW cytotoxic-tracer drug solution or emulsion-injected intratumoral immediately before a cryoablative procedure is not displaced by the ice ball.…”
Section: Effectivenessmentioning
confidence: 99%